Radiosensitivity of colorectal cancer to 90Y and the radiobiological implications for radioembolisation therapy - Lee, B; Abbott, E; Able, S; Thompson, J; Hill, M; Kartsonaki, C; Vallis, K; Falzone, N (IOP Publishing, 2019)
Approximately 50% of all colorectal cancer (CRC) patients will develop metastasis to the liver. 90Y selective internal radiation therapy (SIRT) is an established treatment for metastatic CRC. There is still a fundamental lack of understanding regarding the radiobiology underlying the dose response. This study was designed to determine the radiosensitivity of two CRC cell lines (DLD-1 and HT-29) to 90Y β− radiation exposure, and thus the relative effectiveness of 90Y SIRT in relation to external beam radiotherapy (EBRT). A 90Y-source dish was sandwiched between culture dishes to irradiate DLD-1 or HT-29 cells for a period of 6 d. Cell survival was determined by clonogenic assay. Dose absorbed per 90Y disintegration was calculated using the PENELOPE Monte Carlo code. PENELOPE simulations were benchmarked against relative dose measurements using EBT3 GAFchromic™ film. Statistical regression based on the linear-quadratic model was used to determine the radiosensitivity parameters α and β using R. These results were compared to radiosensitivity parameters determined for 6 MV clinical x-rays and 137Cs γ-ray exposure. Equivalent dose of EBRT in 2 Gy (EQD2) and 10 Gy (EQD10) fractions were derived for 90Y dose. HT-29 cells were more radioresistant than DLD-1 for all treatment modalities. Radiosensitivity parameters determined for 6 MV x-rays and 137Cs γ-ray were equivalent for both cell lines. The α/β ratio for 90Y β−-particle exposure was over an order of magnitude higher than the other two modalities due to protraction of dose delivery. Consequently, an 90Y SIRT absorbed dose of 60 Gy equates to an EQD2 of 28.7 and 54.5 Gy and an EQD10 of 17.6 and 19.3 Gy for DLD-1 and HT-29 cell lines, respectively. We derived radiosensitivity parameters for two CRC cell lines exposed to 90Y β−-particles, 6 MV x-rays, and 137Cs γ-ray irradiation. These radiobiological parameters are critical to understanding the dose response of CRC lesions and ultimately informs the efficacy of 90Y SIRT relative to other radiation therapy modalities.